2019
DOI: 10.1016/j.progsolidstchem.2019.100252
|View full text |Cite
|
Sign up to set email alerts
|

Joint stereochemical and ab initio overview of SnII electron lone pairs (E) and F−(E) triplets effects on the crystal networks, the bonding and the electronic structures in a family of tin fluorides

Abstract: The stereochemistry of 5s 2 (E) lone pair of divalent Sn (Sn II designated by M*) and the lone pair triplet around the luorine ions are examined complementarily with stereo-chemical approach and ab initio quantum investigations focusing on the electron localization and pertaining electronic structure properties, obtained within Density Functional Theory (DFT) and derived Electron Localization Function (ELF) mapping. The review completes a series of former ones focusing on the stereochemical role played by elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…We now observe clear trends: the RDs decrease down a group and increase from left to right in a period. These results confirm the previous work (Galy et al, 1975) and generalize it to a large number of compounds. The decrease of the relative M*-LP distance down a group means that, for a given cation charge, the smaller the core radius, the larger the M*-LP distance.…”
Section: Evolutions Of the M*-lp Distances And Lp Radii Within The Pesupporting
confidence: 92%
See 4 more Smart Citations
“…We now observe clear trends: the RDs decrease down a group and increase from left to right in a period. These results confirm the previous work (Galy et al, 1975) and generalize it to a large number of compounds. The decrease of the relative M*-LP distance down a group means that, for a given cation charge, the smaller the core radius, the larger the M*-LP distance.…”
Section: Evolutions Of the M*-lp Distances And Lp Radii Within The Pesupporting
confidence: 92%
“…Later, an ab initio study (Suehara et al, 2004b) performed on a TeO 4 H 4 molecule, with geometry close to the TeO 4 disphenoid found in -TeO 2 , also revealed an electronic density maximum at $0.6 Å from the core. The studies of Galy et al (1975) and Christy & Mills (2013) Local environments of Te 4+ cations found in TeO 2 -based crystal structures: (a) usual environments and (b) atypical environments. Te 4+ cores are shown in black and O 2À anions in red; blue arrows represent the Te 4+ LP and the longest Te-O bonds are drawn with dashed lines.…”
Section: Evolutions Of the M*-lp Distances And Lp Radii Within The Pementioning
confidence: 99%
See 3 more Smart Citations